Education - Ango, Samuel P.; Rutoro, Ester (African Public Theology, 2020)
Nelson Mandela said, "education is the most powerful weapon which you can use to change the world." This is true universally, but especially so in Africa which had the world's highest birth rate with the result that more than 60 percent og the population is under tge age of 25. The demand for schooling is high, and most African parents say that they value education and want their children to receive a good education. But the realitites on the ground are dire. So before we van look at what public theology has to say about ducation, we need to understand wgat the problems are and why Africa's levels of education are so low.